SCIENTIFIC APPROACH AND COMMUNICATIVE COMPETENCE OF THE ENGLISH TEXTBOOK “FORWARD” - Nanang Lesmana (INFERENCE: Journal of English Language Teaching, 2022)
Textbook has an important role in the process of teaching and learning activities. Therefore, this study aims to examine: 1) The Scientific Approach of the English textbook “Forward”; and 2) the Communicative Competence of the English textbook “Forward”. The method used in this study was a content analysis method in which it is a kind of descriptive qualitative research. The results of this study indicated that the textbook had implemented all stages of the Scientific Approach consisting of 80.77% observing activities; 58% of questioning activities, 70.77% of exploring activities, 75% of reasoning/associating activities, and 35.90% of communicating activities. Related to the Communicative Competence, the textbook consists of 23.81% elements of Discourse Competence, 23.81% elements of Linguistic Competence: 4.76% elements of Actional Competence, 14.29% elements of Sociocultural Competence, and 0% elements of Strategic Competence.